Podejście prognostyczne w badaniach naukowych - Czarkowski, Andrzej (Wydział Prawa i Administracji UAM, 1988)
One of the conditions of ensuring to prognoses the image of the future consistent with the reality is the way of treating the future by means of a „prognostic approach". It is seldom explicated in research, yet it functions in a more or less conscious way. In effect it is either characterized by a weak theoretical justification or it is burdened with narrow pragmatism. Each prognosis should be based on a so-called initial state, i.e. the knowledge of a researched object. Otherwise one will obtain a forecast, not a prognosis. An important problem to be considered here is the question about relations between a prognosis and the future reality. A prognosis creates the imagined reality. However, the above does not settle the question whether the propositions about the future are true or false. Another question concerns the character of prognostic procedure. One deals here with prognostic hypothetism referring to objects which will appear in future or to objects which already exist yet may undergo changes or disappear later. Prognostic hypothetism is a justified explanation of the future reality. Sometimes in research praxis it happens that the object of a prognosis is treated as an autonomous entity, with an acting human being eliminated from the analysis. In order to avoid the above, a prognostic approach should comprise both bojective and subjective factors as basic elements of a social process. An objective factor denotes the results of human activities, material bases and conditions of those activities. A subjective factor denotes puposes, values, the state of knowledge of the reality and the entire sphere of motivation to which also the prognosis about the future belongs. Needless to say, it does not mean that the future will be in agreement with the intentions of acting subjects. Treating both factors integrally not only defines their role in creating the future, but is the basis for explaining it as well.
Prognostic approach in scientific research